Peripheral vasoconstriction is not elevated during hyperreactive responses to the cold pressor test: a cross-sectional study - Jon Stavres; Anabelle Vallecillo-Bustos; Sarah Parnell; Ryan S. Aultman; Ta’Quoris A. Newsome; Sydney H. Swafford; Abby T. Compton; Rhett C. Schimpf; Sophia N. Schmidt; Carstell Lee; Austin J. Graybeal (Frontiers in Physiology)
BackgroundIndividuals demonstrating increases in systolic systolic blood pressure or diastolic diastolic blood pressure blood pressure of at least 15 mmHg are considered hyperreactors to the cold pressor test (CPT). However, it remains unclear if peripheral vasoconstriction is similarly exaggerated during the CPT in these individuals.MethodsFifty-five individuals (54.5% non-White, 67.3% female) performed a single-visit study including a 2-min CPT of the foot, a 2-min bout of rhythmic handgrip exercise ([HG] 25% maximal voluntary contraction), and a 2-min combined trial (CPT + HG). Beat-by-beat heart rate (HR), blood pressure, and forearm blood flow (FBF) were continuously recorded, and vascular conductance (FVC) was calculated as FBF/mean arterial pressure (MAP).ResultsHyperreactors (n = 21) demonstrated exaggerated increases in blood pressure and rate pressure product during the CPT compared to normoreactors (n = 34; all p < 0.001), while no significant differences were observed for ΔFBF (f = 1.33, p = 0.259) or ΔFVC responses (f = 2.10, p = 0.083). Results also indicated a blunted increase in ΔMAP during the CPT + HG trial compared to the CPT only trial in hyperreactors (f = 6.95, p < 0.001), which was not observed in normoreactors (f = 0.982, p = 0.420), and a blunted ΔFVC response during the CPT + HG trial in hyperreactors compared to normoreactors (f = 2.57, p = 0.039). When analyzed separately, the blood pressure responses to HG exercise were also significantly exaggerated in hyperreactors compared to normoreactors (all p < 0.001), while ΔFBF and ΔFVC responses were not (both p ≥ 0.701).ConclusionThese findings indicate that hyperreactive blood pressure responses to the CPT are not accompanied by increased peripheral vasoconstriction. Moreover, handgrip exercise attenuates hyperreactive blood pressure responses to the CPT.